Integrating Tradition and Modernity: Educational Management Strategies - Qusairi, Ahmad; Fikri, Heykal; Akbar, Muhammad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Islamic educational institutions face the ongoing challenge of balancing traditional values with modern educational management strategies to enhance both academic performance and character development. This study aims to explore how Madrasah Aliyah Hidayaturrahman integrates these elements to address this dual objective. Using a qualitative descriptive method, data were collected through observations, semi-structured interviews, and document analysis. The findings reveal that a student-centered and collaborative management approach, coupled with structured teacher training programs, fosters creativity, inclusivity, and academic excellence. The study highlights that integrating traditional Islamic values with contemporary methodologies not only improves learning outcomes but also strengthens the institution’s ability to adapt to modern educational demands. This research contributes to the broader discourse on Islamic education by providing a practical model for other institutions to harmonize tradition and modernity effectively.